2023
DOI: 10.3390/antiox12030686
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and the Risk of Metabolic Syndrome in the ‘Seguimiento Universidad de Navarra’ Project

Abstract: (1) Background: Metabolic Syndrome (MetS) affects over a third of the United States population, and has similar prevalence in Europe. Dietary approaches to prevention are important. Coffee consumption has been inversely associated with mortality and chronic disease; however, its relation to the risk of MetS is unclear. We aimed to investigate the association between coffee consumption and incident MetS in the ‘Seguimiento Universidad de Navarra’ cohort. (2) Methods: From the SUN project, we included 10,253 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…While previous prospective cohort studies examining the preventive effects of coffee intake on MetS were limited, their findings were inconsistent (6,(10)(11)(12)(13). Most of the previous cohort studies failed to establish a significant connection between coffee consumption and the development of MetS (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous prospective cohort studies examining the preventive effects of coffee intake on MetS were limited, their findings were inconsistent (6,(10)(11)(12)(13). Most of the previous cohort studies failed to establish a significant connection between coffee consumption and the development of MetS (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…of typical hot-brewed or reconstituted instant coffee daily is associated with a reduced risk of various illnesses, including diabetes, CVD, and specific metabolic abnormalities like obesity and hypertension (8,9). However, previous research on the relationship between coffee consumption and the presence of MetS showed conflicting results (6,(9)(10)(11)(12)(13)(14)(15)(16). One significant limitation in many of these studies has been the absence of information about physical activity (PA), a crucial factor that can profoundly influence metabolic health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee is a widely consumed beverage rich in bioactive compounds with positive impacts on health, including the reduction of incidence of Parkinson disease, Alzheimer disease, certain types of cancer, type 2 diabetes, and obesity (Carneiro et al, 2021; Corbi‐Cobo‐Losey et al, 2023; Safe et al, 2023). In a large prospective study, Liu et al (2022) found that coffee consumption reduced the risk of death from various causes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested a potential protective effect of coffee consumption against metabolic syndrome. Coffee is rich in antioxidants and compounds that may improve insulin sensitivity and reduce in ammation (19,20). Whole-grain cereals, especially those high in ber, can be bene cial for metabolic health.…”
Section: Introductionmentioning
confidence: 99%